The Impact and Mechanism of Femvertising in Male Consumers’ Gift Purchasing Intention - Siyu Yang; Zengrui Xiao; Diqing Qian (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
Femvertising is increasingly being used by brands to showcase their values and attract consumers, especially in the fashion industry. Previous studies mainly focused on its impact on female consumers, while the perceptions and responses of male consumers are usually ignored. Focusing on the context of men purchasing women’s clothes as gifts, this study aimed to explore the impact of femvertising on male consumers’ gift purchasing intention and reveal the mechanism, with the mediating effects of female empowerment and brand hypocrisy and the moderation effect of gift recipient. A situational experiment was conducted to acquire data, and hypotheses were tested with regression analysis and the bootstrapping method. The results demonstrated that the total effect of femvertising on male consumers’ gift purchasing intention is not significant, but there is a positive mediating effect of female empowerment and a negative mediating effect of brand hypocrisy, and the mediating effect of female empowerment is stronger for a communal relationship (versus an exchange relationship).